2015
DOI: 10.1093/ajh/hpv140
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Pressure Control Fails to Account for Most Distending Pressure-Independent, Age-Related Aortic Hemodynamic Changes in Adults

Abstract: Brachial BP control in the general population fails to account for most distending pressure-independent, age-related changes in aortic hemodynamics across the adult lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
2
8
0
1
Order By: Relevance
“…In this regard, it was previously described that early in life, there is a rapid increase in stroke volume, reaching a peak at ∼20 y, followed by a slow decline from the beginning of the third decade of life ( Cattermole et al, 2017 ; Zócalo et al, 2020 ). The (relative) Pf stability observed within the range of 30 and 60 y of age is in agreement with previous findings in subjects with controlled and uncontrolled blood pressure ( Hodson et al, 2016 ), in healthy and unhealthy subjects ( Li et al, 2019 ) and in subjects with cardiovascular disease ( Namasivayam et al, 2016 ). On the other hand, whereas in this work, the increase in Pf after 70 y of age was discrete, works that included subjects with cardiovascular disease and/or exposed to CRFs described a greater (steeper) increase ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this regard, it was previously described that early in life, there is a rapid increase in stroke volume, reaching a peak at ∼20 y, followed by a slow decline from the beginning of the third decade of life ( Cattermole et al, 2017 ; Zócalo et al, 2020 ). The (relative) Pf stability observed within the range of 30 and 60 y of age is in agreement with previous findings in subjects with controlled and uncontrolled blood pressure ( Hodson et al, 2016 ), in healthy and unhealthy subjects ( Li et al, 2019 ) and in subjects with cardiovascular disease ( Namasivayam et al, 2016 ). On the other hand, whereas in this work, the increase in Pf after 70 y of age was discrete, works that included subjects with cardiovascular disease and/or exposed to CRFs described a greater (steeper) increase ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, in our knowledge, there are no works assessing waveform-derived indexes’ variations (as a continuous) considering data from different age-stages and their transitions (childhood-adolescence-adulthood). It is to note that studies that aimed at analyzing age-related differences do not allow for their adequate and comprehensive characterization, as they (i) considered small numbers of subjects [e.g., n = 65 ( Hughes et al, 2013 ), n = 267 ( Yu et al, 2020 )], (ii) did not exclude subjects with cardiovascular disease or exposed to CRFs [e.g., cardiology outpatients ( Namasivayam et al, 2016 ), unhealthy or diseased subjects ( Torjesen et al, 2014 ; Hodson et al, 2016 ; Li et al, 2019 ), and subjects with CRFs ( Mitchell et al, 2004 ; Hughes et al, 2013 ; Hickson et al, 2016 ; Wilenius et al, 2016 ; Gómez-Sánchez et al, 2020 ; Yu et al, 2020 )]; (iii) compared “mean values” of groups comprising subjects of wide age ranges (e.g., 5–7 years (y) ( Segers et al, 2007 ; Janner et al, 2010 ; Hodson et al, 2016 ) or 10 y ( Kelly et al, 1989 ; Mitchell et al, 2004 ; McEniery et al, 2005 ; Torjesen et al, 2014 ; Hickson et al, 2016 ; Namasivayam et al, 2016 ; Solanki et al, 2018 ; Li et al, 2019 ; Yu et al, 2020 ) of difference in the age of subjects belonging to the same group); (iv) considered only adults within a limited age range (e.g., 40–70 y, grouped by decades) ( Li et al, 2019 ), and (v) in general, did not consider subjects under 18–20 years of age. In this context, it should be noted that the need for RIs for vascular parameters in children and adolescents is now well-recognized and is considered necessary to extend their use in clinical practice ( Climie et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that elasticity of the arteries is impaired with advanced age. 22 , 23 Similarly, it has been reported that increased resting heart rate is associated with aortic stiffness and atherosclerosis. 24 , 25 Our study supports these results.…”
Section: Discussionmentioning
confidence: 95%
“…cBP is determined by the complex interaction between aortic compliance, elasticity and the resistance arteries' ability to channel blood flow in accordance with tissue needs (Stephen Hedley and Phelan 2017). Hence, cBP is superior to brachial blood pressure in identifying changes in vascular functional parameters (Hodson et al 2016) and cardiovascular risk (Williams et al 2006;Roman et al 2007;Cheng et al 2013;Fan et al 2016;Herbert et al 2014). Particularly in young men, central diastolic BP, but not peripheral systolic pressure, is a predictor of cardiovascular risk (Wilkinson et al 2001).…”
Section: Discussionmentioning
confidence: 99%